Saturated and aromatic aldehydes originating from skin and cutaneous bacteria activate the Nrf2‐keap1 pathway in human keratinocytes. Issue 10 (17th May 2020) - Ron‐Doitch, Sapir; Soroka, Yoram; Frusic‐Zlotkin, Marina; Barasch, Dinorah; Steinberg, Doron; Kohen, Ron
Abstract: Skin homeostasis is constantly challenged by environmental factors, affecting its delicate redox balance. The skin is also home to a wide variety of bacterial species, including Staphylococci . The cutaneous redox state is governed by the Nrf2‐keap1 pathway, which is responsible for the induction of phase II cytoprotective enzymes, thus sustaining a healthy oxidative state. As part of normal metabolism, both bacteria and cutaneous tissue emit copious amounts of volatile organic compounds (VOCs), one subgroup of which are aldehydes. α, β‐unsaturated aldehydes are known activators of Nrf2‐keap1 pathway by direct oxidation of the keap1 protein. However, we did not encounter reports of Nrf2 activation by saturated or aromatic aldehydes, neither bacteria nor skin‐derived. We hypothesized that non–α, β‐unsaturated aldehydes derived from skin or cutaneous bacteria may act as Nrf2‐keap1 pathway activators and therefore afford protection against environmental insults. The saturated aldehydes nonanal and decanal (known skin metabolites) and the aromatic aldehyde benzaldehyde (known skin and Staphylococcus epidermidis metabolite) were shown to induce the Nrf2‐keap1 pathway in human keratinocytes. We also identified a newly described aromatic aldehyde, 3‐furaldehyde (3‐FA), emitted from S. aureus and S. epidermidis cultures, which also activated the pathway. Moreover, Nrf2‐keap1 induction led to a significant protection against UVB‐induced apoptosis. The mechanism involved in this activation has been partially elucidated. This work emphasizes the importance of cutaneous bacteria, as well as healthy skin lipid peroxidation processes in the maintenance and regulation of the cellular antioxidant response, namely with regard to coping with environmental stressors.